2015
DOI: 10.1073/pnas.1501985112
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and dynamics of the Gag polyprotein of the human immunodeficiency virus 1 studied by NMR spectroscopy

Abstract: Assembly and maturation of the human immunodeficiency virus type 1 (HIV-1) are governed by the Gag polyprotein. Here we study the conformation and dynamics of a large HIV-1 Gag fragment comprising the matrix, capsid, spacer peptide 1 and nucleocapsid domains (referred to as ΔGag) by heteronuclear multidimensional NMR spectroscopy. In solution, ΔGag exists in a dynamic equilibrium between monomeric and dimeric states. In the presence of nucleic acids and at low ionic strength ΔGag assembles into immature virusl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
63
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 48 publications
8
63
1
Order By: Relevance
“…1A). ΔGag exhibits a monomer-dimer equilibrium at high ionic strength (K dimer ∼35 μM at ≥300 mM NaCl), but at low salt (≤100 mM NaCl) forms immature virus-like particles (3). We also made use of the construct, ΔGag W316A M317A (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). ΔGag exhibits a monomer-dimer equilibrium at high ionic strength (K dimer ∼35 μM at ≥300 mM NaCl), but at low salt (≤100 mM NaCl) forms immature virus-like particles (3). We also made use of the construct, ΔGag W316A M317A (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These encounter complexes are likely to have a significant impact on the (26) suggested that the six-helix bundle formed by SP1 (27) in immature Gag assemblies may block access to the CAjSP1 junction, thereby slowing down the proteolysis at this site. However, SP1 and neighboring residues are intrinsically disordered and fully accessible in solution in the context of ΔGag, as evidenced by NMR chemical shifts, relaxation parameters, and backbone amide RDCs (3,24), and yet hydrolysis at the CAjSP1 junction is remarkably slow in vitro (compare Fig. 1B), even when mutated to the sequence of the SP1jNC junction (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RSV protease was purified as previously described (26), and stored at 1 mg/ml in buffer (20 mM MES [pH 6.5], 100 mM NaCl, 2 M ZnCl 2 ) at Ϫ80°C until use. For digestions of protein with GT25 oligonucleotide, protein was mixed with oligonucleotide as described for VLP assembly, and the mixture was incubated for 1 h prior to the addition of protease (a method similar to one used to analyze HIV Gag cleavage [27]). PR digestions were performed in buffer (20 mM MES [pH 6.5], 100 mM NaCl) at a 1:1 mass ratio of PR to Gag⌬MBD protein for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Essential information about CA molecular structure and lattice structure has been obtained from a large number of investigations by electron microscopy (2-4, 7), x-ray crystallography (5,6,8,(17)(18)(19)(20), and multidimensional nuclear magnetic resonance (NMR) spectroscopy of soluble monomeric and dimeric constructs (21)(22)(23)(24)(25)(26)(27)(28)(29). Results from these investigations show that CA is primarily ␣-helical, with independently folding N-terminal (helices 1-7) and C-terminal (helices 8 -11) domains (NTD and CTD), connected by a short linker that allows the relative orientations of NTD and CTD to vary widely in the unassembled, soluble state.…”
mentioning
confidence: 99%